Pemberdayaan Santri melalui Aplikasi Kedungsantren Mobile dalam Pengelolaan Keuangan di PPSD Kedungsantren Desa Campurejo Kabupaten Bojonegoro - Juliyani, Erly; Musbikhin, Musbikhin; Burhanuddin, Burhanuddin (Opportunity Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The development of information technology is something that cannot be avoided in the current era. Technological developments have influenced several aspects, such as in education. A software that supports the course of education is a way to improve the quality of education. It is time for schools to develop an effective and efficient information system that handles school administration. PPSD Kedungsantren in payment of tuition still uses the manual system. So that at this time the empowerment of students was carried out through the Kedungsantren Mobile application in financial management at PPSD Kedungsantren. The empowerment of students is carried out for one month using the ABCD (Asset Based Community Development) method. The assets owned are human resources who are ready to run the KDS mobile application. The method used is Discovery, Dream, Design, Define, and Destiny, where the method is a form of ABCD approach stages. The result of this empowerment is the creation of the Kedungsantren Mobile application which aims to make it easier to pay tuition fees